Strengthening Indonesia’s Maritime Safety Governance: Insights From Ship Accident Trends and Regulatory Oversight - Riyadi, Slamet; Erliyani, Dian (Jurnal Kebijakan Sosial Ekonomi Kelautan dan Perikanan, 2025)
The high rate of ship accidents highlights a persistent gap between safety regulations, supervision, and field implementation, making maritime accidents a continuing challenge for Indonesia’s shipping safety system. This study examines the key components influencing maritime safety governance and identifies strategic priorities for strengthening regulation and oversight. Using the SWOT–AHP (Strengths, Weaknesses, Opportunities, and Threats–Analytic Hierarchy Process) method, internal and external factors were assessed through pairwise comparisons to establish consistent priorities. The findings indicate that international and national regulations (31.1%), maritime education and training (14.8%), and Port State Control (PSC) supervisory capacity (13.6%) are the most critical factors, while structural weaknesses such as low inspection frequency (7.2%) and the lack of safety culture (3.7%) remain major barriers. Opportunities in digital monitoring (2.6%) and threats from extreme weather (2.5%) underscore the need for adaptive, risk-based strategies. The novelty of this study lies in integrating the SWOT–AHP framework with Risk-Based Management (RBM) and strategic management theory to produce a measurable strategic priority map that directly links quantitative evidence to policy planning, implementation, and evaluation. Furthermore, the study introduces a time-phased, multi-actor policy strategy comprising short-term (1–3 years) initiatives, such as regulatory harmonization, digital monitoring, and capacity building led by the Ministry of Transportation and long-term (4–10 years) reforms emphasizing institutional integration, AI-based predictive safety systems, and national safety culture development led by cross-ministerial coordination. This combined approach provides a practical and data-driven foundation for achieving adaptive, measurable, and sustainable maritime safety governance in Indonesia.